Productive inefficiency in patriarchal family farms: evidence from Mali - Tatiana Goetghebuer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In Mali, there exist various farm-cum-family structures, so that agricultural production occurs on plots controlled by different members of the household. In this paper, we want to lay emphasis on the under-researched differentials between collective and individual plots (attended by male or female farmer) in the context of extended family farms using input and output first hand data collected in the south-eastern part of Mali. First, we find that land yields are significantly larger on (male) private plots than on common plots with similar characteristics planted to the same crop in the same year after all appropriate controls have been included. And, second, we bring strong suggestive evidence that a moral hazard-in-team problem exists on the collective fields (yet only with regard to care-intensive crops) that could explain their relatively poor performance.
Keywords: D13; D57; J12; O12; O13; Q12; Q15; R20; 330; Land productivity; family structure; moral-hazard-in-team problem; collective